Numerical Analysis of Sensitivity of SAW Structure to the Effect of Toxic Gases - HEJCZYK, Tomasz; PUSTELNY, Tadeusz; WSZOŁEK, Bartlomiej; JAKUBIK, Wieslaw; MACIAK, Erwin (Archives of Acoustics, 2016)
The paper presents the results of numerical analysis of the SAW gas sensor in the steady and non-steady states. The effect of SAW velocity changes vs surface electrical conductivity of the sensing layer is predicted. The conductivity of the porous sensing layer above the piezoelectric waveguide depends on the profile of the diffused gas molecule concentration inside the layer. The Knudsen’s model of gas diffusion was used. Numerical results for the effect of gas CH4 on layers: WO3, TiO2, NiO, SnO2 in the steady state and CH4 in the non-steady state in recovery step in the WO3 sensing layer have been shown. The main aim of the investigation was to study thin film interaction with target gases in the SAW sensor configuration based on simple reaction-diffusion equation. The results of the numerical analysis allow to select the sensor design conditions, including the morphology of the sensor layer, its thickness, operating temperature, and layer type. The numerical results basing on the code elaborated numerical system (written in Python language), were analysed. The theoretical results were verified and confirmed experimentally.